2016
DOI: 10.55095/achot2016/012
|View full text |Cite
|
Sign up to set email alerts
|

Eleven-Year Experience with Total Ankle Arthroplasty

Abstract: PURPOSE OF THE STUDYTotal joint replacement is one of the options in surgical treatment of advanced ankle arthritis. It allows the ankle to remain mobile but, unfortunately, it does not provide the same longevity as total knee or hip replacements. Therefore, decisions concerning the kind of treatment are very individual and depend on the clinical status and opinion of each patient. MATERIAL AND METHODSA total of 132 total ankle replacements were carried out in the period from 2004 to 2015. The prostheses used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Pyevich et al [ 67 ] also showed that patients with post-traumatic osteoarthritis reported significantly more pain than patients with primary osteoarthritis after total ankle replacement with agility prostheses. Similarly, Popelka et al [ 68 ] reported significantly lower American Orthopaedic Foot and Ankle Society (AOFAS) scores in patients with post-traumatic osteoarthritis than in patients with primary osteoarthritis after total ankle replacement. However, as the majority of patients in our analysis could not be assigned to an osteoarthritis type due to a lack of ICD specification, these results must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Pyevich et al [ 67 ] also showed that patients with post-traumatic osteoarthritis reported significantly more pain than patients with primary osteoarthritis after total ankle replacement with agility prostheses. Similarly, Popelka et al [ 68 ] reported significantly lower American Orthopaedic Foot and Ankle Society (AOFAS) scores in patients with post-traumatic osteoarthritis than in patients with primary osteoarthritis after total ankle replacement. However, as the majority of patients in our analysis could not be assigned to an osteoarthritis type due to a lack of ICD specification, these results must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%